La prison de Socrate: la dernière leçon du maître - Agne, Djibril (Gerión. Revista de Historia Antigua, 2008)
Socrates fully enjoyed his freedom as a citizen in Athens, a city where everybody knew him. He used to go to public and private places accompanied by his disciples, his fellow country people, and foreigners. The 399 trial led his to prison which became his last teaching arena. However, he did not at all lose there his freedom of thought, which he fully exploited with his disciples. That last lesson from the Master took place from sunrise to sunset, an entire day of psychological pressure for his kin and disciples. Such a pressure was made more intense by the announcement of the return of Apollo’s boat, which marked Socrates’s imminent end. In that prison environment, the philosopher displayed more serenity than his kin and disciples who were wracked by anguish and pain. Socrates’s serenity showed also in the way in which he conducted his discussions centered on themes that were as varied as rich. As a matter of fact, he felt very free in prison in which he debated on philosophy and on life in general. Socrates faced death as a genuine philosopher ‘true to himself and internally free’. He convinced his disciples about the fact that death is not an end in itself, but just a passage from one world to another; from material life to spiritual life.